PENGARUH STRATEGI KEUNGGULAN BIAYA DAN DIFERENSIASI DALAM RANGKA MENINGKATKAN VOLUME PENJUALAN PADA BISNIS OPTIK DI KOTA PEKANBARU - Agung Perdana Putra; Rina Selva Johan; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstack: This study aims to determine the effect of cost advantage and differentiation strategy in order to increase sales volumes in the optical business in the city pekanbaru.Populasi in this study is a business venture or optical totaling 59 optics in Pekanbaru 2015, respondents in this study is the owner or employee optics. Samples were obtained using the formula slovin total of 37 optical, samples were taken by using random sampling techniques. Data were collected using a questionnaire or a questionnaire. Data were analyzed using multiple linear regression analysis, t test and F test with significance level of 0.05%. It is based on the analysis results, in which the calculation results show F count> F table (12.260> 3.276), followed by t-test to determine whether each independent variable (Strategies cost advantage and differentiation) effect on the dependent variable (Volume Sales). The results of this study partially shows cost advantage and a significant positive effect on sales volume this is evidenced by tcount> t table (2.646> 1.691) .Next differentiation strategy is positive and significant impact on sales volume this is evidenced by the value of t> t table ( 4.066> 1.691). The predictive ability of these two variables on sales volume in this study amounted to 41.9%, while the remaining 58.1% is influenced by other factors not examined in this study.Keywords: strategies excellence, differentiation and volume sales